THE PROFILE OF STUDENTS' CREATIVITY AND STUDENTS' PARTICIPATION BY USING 5E LEARNING MODEL IN LEARNING HUMAN RESPIRATORY SYSTEM - Hikmatunisa, Nenden Permas (2015)
This research investigated the profile of 5E learning model as constructivist approach toward students' creativity and students' participation in learning human respiratory system. The method used in this research was descriptive method. The sample was taken based on the purposive sampling, the class that use is consist of 25 students of grade 7 in an International School in Bandung Barat District. Students' creativity data got through rubric scoring, while students' participation got through rubric scoring and questionnaire. Based on data analysis, it is shown that the students experienced 5E learning model. Furthermore, the students were active to participate in classroom activities with 96% students can contribute in discussion, 92% students have ability skill to work in group, but only 58,67% have ability in communication skill. Meanwhile, the result of students' creativity was in medium level of creativity. The average score of groups' creativity scoring is 64,40% for novelty. In resolution, 57,70%. Then, in elaboration and synthesis is 77,80%. Penelitian ini bertujuan untuk meginvestigasi model pembelajaran 5E sebagai pendekatan constructivist terhadap kreativitas siswa dan juga partisipasi siswa dalam mempelajari sistem pernapasan pada manusia. Metode yang digunakan dalam penelitian ini adalah deskriptive. Adapun sample yang digunakan adalah purposive sampling, kelas yang digunakan terdiri dari 25 siswa kelas 7 pada salah satu sekolah internasional di Kabupaten Bandung Barat. Data kreativitas siswa didapatkan dengan menggunakan rubric scoring dan questionnaire.Berdasarkan data analisis, ditunjukan bahwa siswa telah mendapakan pengalaman belajar dengan menggunakan 5E model. Selain itu, siswa aktif berpartisipasi dikelas yang ditunjukan dengan persentase sebanyak 96% siswa dapat berkontribusi aktif, 92% siswa mempunyai keahlian untuk bekerja secara berkelompok, namun hanya 58,6% mempunyai kemampuan berkomunikasi. Disamping itu, hasil rata-rata dari kreativitas siswa terdapat 64,40% untuk novelty aspek, 57,70% untuk resolution aspek dan 77,80% untuk elaboration and synthesis aspek.